Actual mercury speciation and mercury discharges from coal-fired power plants in Inner Mongolia, Northern China. (15th September 2016) - Tang, Shunlin; Wang, Lina; Feng, Xinbin; Feng, Zhaohui; Li, Ruiyang; Fan, Huipeng; Li, Ke
Highlights: Mercury emissions from coal combustion are in the dominant form of Hg 0 (>85%). Direct and indirect speciated Hg discharge factors of coal-fired power plants were obtained. The maximum of Hg emissions from coal-fired power plants of Inner Mongolia is 24 Mg/y. The largest direct Hg emissions may be the utilization industry of fly ash and gypsum. Abstract: Mercury species distribution in the flue gas from three typical coal-fired power plants have been investigated using a C-5000 sampler for Ontario Hydro Method (OHM) to evaluate specified Hg emission inventories in the largest coal-production province of China, Inner Mongolia. The feed coal, bottom ash, fly ash and gypsum have also been sampled in the field. Mercury emissions are in the dominant form of Hg 0 (>85%). The Hg 2+ (<15%) and the Hg p (<2%) emissions are minor fractions of Hg t in the flue gas. The wet limestone flue gas desulfurization device (WLFGD) showed much higher removal efficiency for Hg 2+ (87–95%) than for the other two Hg species. The input Hg/output Hg varied from 92% to 115% for the tested 3 coal-fried utility boilers during sampling time. We obtained comprehensive Hg discharge factors, including direct atmospheric Hg emission factors and indirect discharge factors of Hg associated with bottom ash, fly ash and gypsum, to the environment, designating the fates of Hg in coal. We estimated the Hg discharges from coal-fired power plants in Inner Mongolia in 2008–2014 and expanded to China. The maximum of direct Hg emissions from coal-fired power plants of Inner Mongolia was 24 Mg in 2012. The Chinese coal-fired power plants emitted directly 100 Mg Hg to the atmosphere every year at the nationwide air control actions. The maximum discharges of Hg associated with fly ash and gypsum of Inner Mongolia was 81 Mg and 11 Mg in 2012, respectively. The national Hg discharges with fly ash and gypsum every year are respectively about 300 Mg and 82 Mg, majority of which may be reemitted to the atmosphere by the utilization industry. Therefore, mercury emissions from coal-fired power plants are not the largest single source of Hg to the atmosphere in normal operation of the current efficient denitrification, particles control and desulfurization devices. Instead, the utilization industry of fly ash and gypsum would be emitting more Hg to the atmosphere.